2016
DOI: 10.1021/jacs.6b05942
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Oxygen Atom Transfer Photocycle from a Diruthenium Oxyanion Complex

Abstract: Three new diruthenium oxyanion complexes have been prepared, crystallographically characterized, and screened for their potential to photochemically unmask a reactive Ru–Ru=O intermediate. The most promising candidate, Ru2(chp)4ONO2 (4, chp = 6-chloro-2-hydroxypyridinate), displays a set of signals centered around m/z = 733 amu in its MALDI-TOF mass spectrum, consistent with the formation of the [Ru2(chp)4O]+ ([6]+) ion. These signals shift to 735 amu in 4*, which contains 18O-labeled nitrate. EPR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 86 publications
2
32
0
Order By: Relevance
“…We have carried out a series of kinetic isotope effect (KIE) experiments to interrogate the nature of the reactive nitrogen species generated during photolysis of 3 (Table 1). Photolysis of 3 in a 1:1 THF/THFd 8 mixture affords a KIE of 2.72 (8). This value is well-matched to KIEs that have been previously measured for Rh 2 -catalyzed C−H amination using iminoiodinanes as nitrene sources.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We have carried out a series of kinetic isotope effect (KIE) experiments to interrogate the nature of the reactive nitrogen species generated during photolysis of 3 (Table 1). Photolysis of 3 in a 1:1 THF/THFd 8 mixture affords a KIE of 2.72 (8). This value is well-matched to KIEs that have been previously measured for Rh 2 -catalyzed C−H amination using iminoiodinanes as nitrene sources.…”
supporting
confidence: 85%
“…6 We have been attracted to synthetic photochemistry as a tool to access authentic reactive intermediates under conditions that allow their characterization without attenuating their reactivity. 7 In contrast to metal oxo and nitrido complexes, which can be generated by photolysis of metal-bound oxyanions 8 and azido ligands, 9 respectively, there are no readily available photoprecursors to metal nitrenoid complexes. Here, we report the development of a new photochemical synthesis of metal nitrenoids, which has enabled the first spectroscopic observation of a Rh 2 nitrenoid intermediate in C−H amination.…”
mentioning
confidence: 99%
“…For example, Berry and co-workers demonstrated that photolysis of Ru 2 (chp) 4 (NO 3 ) (chp = 6-chloro-2-hydroxypyridinate) generated a metal oxo with concomitant release of NO 2 . 13 Similarly, Suslick and co-workers reported that photolysis of Mn(TPP)(NO 3 ) also resulted in metal oxo generation and release of NO 2 . 15 However, it should be noted that in both of these examples the resulting metal oxo was unstable and not isolated.…”
Section: Introductionmentioning
confidence: 96%
“… 12 In our recent synthesis of [Li(12-crown-4)][(NN′ 3 )Ce(O)], the oxo ligand was formed via reduction of a nitrate ligand, in a formal 1e – O-atom transfer process. Several other examples demonstrating the use of nitrate as a 1e – O-atom source have emerged in recent years, 13 16 suggesting that [NO 3 ] – could be a valuable reagent for the generation of f-element oxo complexes. This mode of reactivity can also be promoted with light.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in our laboratory has focused on bimetallic complexes with metal–metal bonds that can support reactive oxo and nitrido groups capable of oxygen atom and nitrene transfer. 4954 A topic of special interest is the role of the metal–metal bond in these complexes, which can be best elucidated by direct comparisons with monometallic analogues (Scheme 1). 53,55…”
Section: Introductionmentioning
confidence: 99%